HUBUNGAN KEPEMIMPINAN MANAJERIAL DENGAN MOTIVASI KERJA PENGASUH DI RUMAH TAHFIZD - Faisal Azhar ,; Sulhati , Sulhati; Salim Aktar , (Juremi: Jurnal Riset Ekonomi, 2025)
The data collection technique in this research is done by collecting instruments, testing instruments, classical assumption test, regression analysis, while the data analysis techniques used are multiple regression, t test, F test, and determination test. The result of the research is that there is a positive and significant relationship between managerial leadership and work motivation, meaning that the higher and more positive the managerial leadership, the higher and more positive the work motivation of caregivers at the Tahfidz PPPA Daarul Qur'an House in Medan, this means that the variations that occur in the leadership variable managerial, 68.2% and 31.8% are influenced by other factors and can be predicted in increasing work motivation.